Analysis of Product Sales Budgeting at PT Sinergi Mandiri Teknikatama Tegal District - Nuraini, Inne Aswinda; Farida, Ida; Fauzi, Ariel Zul (Soedirman Accounting, Auditing and Public Sector Journal, 2024)
The sales budget is the company's main budget before other budgeting is carried out. This study aims to calculate and analyze the preparation of product sales budgets in 2023, which the company has never done budgeting before. The object of research was conducted at PT Sinergi Mandiri Teknikatama which is engaged in the manufacturing business, operating in the LIK Takaru area, Jalan Raya Dampyak KM 04, Dampyak, Kramat District, Tegal Regency. The type of research data used is quantitative data. The source of data obtained is secondary data obtained directly from the company. The preparation of this sales budget uses the trend moment, least square, and Standard Error Forecasting methods to determine which method is closer to suitability, namely by taking the smaller final value. The sales budget for 2023 in Body Hinge 146 T6mm obtained a result of Rp37,518,619 and Handle Control obtained a result of Rp7,906,854.